2021
DOI: 10.3389/fpsyg.2021.740880
|View full text |Cite
|
Sign up to set email alerts
|

What Makes People Hide Knowledge? Influence of Passive Leadership and Creative Self-Efficacy

Abstract: Although numerous studies have been conducted in the field of knowledge sharing with a focus given to its importance, very little attention has been given to knowledge hiding practices. A very few studies have been found to make an attempt to figure out its impact and antecedents. Likewise, the negative role of passive leadership in the project management literature has not been evidenced enough despite its existence in project-based organizations. Both knowledge hiding and passive leadership are the highly ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…The other indicator that did not correlate with social resilience is information access and communication which disagrees with a study by Spialek and Houston (2018) and Rice and Jahn (2019). The finding in Mzuzu can be credited to tendencies by some passive community members privileged with information to hide it (Mubarak et al, 2021) or lack of robust and trustworthy communication channels in the communities (Wilkins et al, 2018). Depriving community members of information puts them at a risk of not taking action on time to early flood warnings and therefore negate consequences of flood disasters (Spialek and Houston, 2018).…”
Section: Continuous Learning and Innovationmentioning
confidence: 68%
“…The other indicator that did not correlate with social resilience is information access and communication which disagrees with a study by Spialek and Houston (2018) and Rice and Jahn (2019). The finding in Mzuzu can be credited to tendencies by some passive community members privileged with information to hide it (Mubarak et al, 2021) or lack of robust and trustworthy communication channels in the communities (Wilkins et al, 2018). Depriving community members of information puts them at a risk of not taking action on time to early flood warnings and therefore negate consequences of flood disasters (Spialek and Houston, 2018).…”
Section: Continuous Learning and Innovationmentioning
confidence: 68%
“…Referring to previous studies, we took the gender, age, education, tenure, position, and company nature of employees as control variables ( Yao et al, 2020 ; Mubarak et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…There are many potential causes of knowledge-hiding practices, but some research has indicated that a lack of participation and engagement in timely information transfer increases knowledge-hiding behaviour (Irum et al, 2020). Knowledge-hiding behaviour is increased when employees are exposed to passive leadership because of chronic stress for employees, and becomes difficult to regain control over their work (Mubarak et al, 2021). On contrary, knowledge-hiding behaviour is diminished when a reciprocal social exchange or a dominant mastery environment exists ( Cerne et al, 2014).…”
Section: Paradoxical Leadership and Knowledge Hidingmentioning
confidence: 99%